(3QSGdI GdSdc Gdbhje aj eYQag GdJbhje ef GdOQ GdjJjes - (3YKeGf GHf SGde GdhQOGfis; (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s ((3Ndjd Hf jMji s)
(3ChdgG (B:s
(3HYO GdOjHGLI Ef ebheGJ GdchGcH GdSjGQI eaJbQ EdjgG ai SGFQ GdCReGf heMJGL EdjgG GdNGU hGdYGe hcGf GdCbQH hGdCSgd s
(3BNQgG (B:s
(3Ydi GNJdGa dejbGJ GdfGS aQCjfG GdfGS Yf LhGgQ GdMceI GdEdgjI eYQVjf hYdi eG ajg GdJda hGdgdGc eTJZdjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B360 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B43 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs